Analysis of the Role and Constraints of Field Supervisors in Kampus Mengajar Program at School (JED (Jurnal Etika Demokrasi), 2024)
This paper aims at  describing the role and identify the obstacles encountered by field supervisors in Kampus Mengajar  program from Batch 3, 4, 5, and 6. The research was conducted in Riau Province with the main informants, namely several DPLs assigned to several elementary schools in Riau province in addition to the students participating in Kampus Mengajar , the research was conducted in the time span of February 2022-December 2023.The research data were collected through interviews and documentation studies. The data analysis technique uses the miles and Huberman model which consists of data collection, verification and data reduction, conclusion drawing. The triangulation technique uses data source triangulation. The results of the study found that there are several roles of DPL, namely (1) communicator, in this role DPLs are required to always coordinate with the Education office and target schools to explain the usefulness and smooth running of Kampus Mengajar  program; (2) facilitator, meaning facilitating students to discuss with each other about the design, implementation and evaluation of Kampus Mengajar  program and; (3) mentor, meaning guiding students to follow the program according to the direction of the ministry but still be able to innovate and develop creativity for the success of the program. The obstacles encountered by DPLs are (1) the remote location of the target schools; (2) Kampus mengajar students who do not obey the rules, making it difficult for DPL positions; (3) the honorarium for Kampus Mengajar program which is compensated and sometimes late in disbursement.
Keywords: Analysis; Role of Constraints; Field Supervisors; Kampus Mengajar; Elementary School.